Foster Kennedy Syndrome: An Atypical Presentation. Issue 12 (December 2015) - Parafita-Fernández, Alberto; Sampil, Marta; Cores, Carlos; Cores, Francisco Javier; Viso, Eloy
ABSTRACT: Purpose: To describe an unusual presentation of Foster Kennedy syndrome (FKS; unilateral optic nerve atrophy with optic nerve edema in the other eye) with optic nerve atrophy and retinal vein occlusion. It is an example of how common clinical features can hide a rare condition or presentation of a disease. Foster Kennedy syndrome is uncommon. Therefore, a space-occupying lesion should be suspected when there is optic atrophy associated with acute pathology of the other eye. Case Report: A 56-year-old man presented with hemiretinal retinal vein occlusion in his right eye. He had previous optic nerve atrophy in his left eye attributed to nonarteritic anterior ischemic optic neuropathy. He lacked cardiovascular or prothrombotic risk factors. Consideration was given whether the presence of contralateral optic atrophy was associated with the retinal vein occlusion. A computed tomographic scan revealed a suprasellar mass. The tumor was excised and identified as meningioma. Conclusions: Although typical FKS would present with optic nerve atrophy and contralateral optic nerve edema secondary to an intracranial mass, in this case, edema was replaced by a hemiretinal vein occlusion. In optic atrophy that does not show characteristic visual field alterations, typical symptoms, or the classic evolution of a given disease, diagnostic imaging may reveal the etiology. As FKS is uncommon, when there is optic atrophy associated with acute pathology of the other eye, a space-occupying lesion should be suspected.